HECS and HECS-HELP: equity Issues - Birch, E.; Miller, Paul (Routledge, 2006)
There have been many changes to the Higher Education Contribution Scheme (HECS) since itsintroduction in 1989. The most significant of these is possibly the reforms announced in the 2003Federal Budget, which allow universities to increase the contributions required of students by up to25%. This paper considers the distribution of deferred HECS liabilities according to thesocioeconomic status of students. An algorithm is presented for converting area-level data to itsindividual-level equivalent. It is found that students of lower socioeconomic status defer a muchlarger proportion of their HECS than students of higher socioeconomic status. The adverse sideeffects of HECS identified in the literature will therefore be more acute for low socioeconomicstatus background students than for their wealthier counterparts.